2021
DOI: 10.1007/s00023-021-01108-2
|View full text |Cite
|
Sign up to set email alerts
|

The Case Against Smooth Null Infinity I: Heuristics and Counter-Examples

Abstract: This paper initiates a series of works dedicated to the rigorous study of the precise structure of gravitational radiation near infinity. We begin with a brief review of an argument due to Christodoulou (in: The Ninth Marcel Grossmann Meeting, World Scientific Publishing Company, Singapore, 2002) stating that Penrose’s proposal of smooth conformal compactification of spacetime (or smooth null infinity) fails to accurately capture the structure of gravitational radiation emitted by N infalling masses coming fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(87 citation statements)
references
References 40 publications
(92 reference statements)
3
84
0
Order By: Relevance
“…The choice for these data was in turn motivated by an argument due to D. Christodoulou [2], which showed that the assumption of Sachs peeling and, thus, of (conformally) smooth null infinity, is incompatible with the no incoming radiation condition and the prediction of the quadrupole formula for N infalling masses from i − . Indeed, we proved that the solutions from [1] described above are not only in agreement with the quadrupole formula (which predicts that ∂ u (rφ) ∼ |u| −2 near i 0 ), but also lead to logarithmic terms in the asymptotic expansion of ∂ v (rφ) as I + is approached, thus contradicting the statement of Sachs peeling that such expansions can be expanded in powers of 1/r. Roughly speaking, we obtained for the spherically symmetric mode φ 0 that if the limit lim…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…The choice for these data was in turn motivated by an argument due to D. Christodoulou [2], which showed that the assumption of Sachs peeling and, thus, of (conformally) smooth null infinity, is incompatible with the no incoming radiation condition and the prediction of the quadrupole formula for N infalling masses from i − . Indeed, we proved that the solutions from [1] described above are not only in agreement with the quadrupole formula (which predicts that ∂ u (rφ) ∼ |u| −2 near i 0 ), but also lead to logarithmic terms in the asymptotic expansion of ∂ v (rφ) as I + is approached, thus contradicting the statement of Sachs peeling that such expansions can be expanded in powers of 1/r. Roughly speaking, we obtained for the spherically symmetric mode φ 0 that if the limit lim…”
mentioning
confidence: 73%
“…
In this paper, we expand on results from our previous paper "The Case Against Smooth Null Infinity I: Heuristics and Counter-Examples" [1] by showing that the failure of "peeling" (and, thus, of smooth null infinity) in a neighbourhood of i 0 derived therein translates into logarithmic corrections at leading order to the wellknown Price's law asymptotics near i + . This suggests that the non-smoothness of I + is physically measurable.More precisely, we consider the linear wave equation g φ = 0 on a fixed Schwarzschild background (M > 0), and we show the following: If one imposes conformally smooth initial data on an ingoing null hypersurface (extending to H + and terminating at I − ) and vanishing data on I − (this is the no incoming radiation condition), then the precise leading-order asymptotics of the solution φ are given by rφ| I + = Cu −2 log u + O(u −2 ) along future null infinity, φ| r=R>2M = 2Cτ −3 log τ + O(τ −3 ) along hypersurfaces of constant r, and φ| H + = 2Cv −3 log v+O(v −3 ) along the event horizon.
…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Smoothness of null infinity is historically a complicated problem in general relativity, see eg. [33] for a recent discussion. More work is clearly needed to understand our result fully, here we will make one elementary comment about Schwarzschild black holes.…”
Section: Black Holes and Log Fall-offsmentioning
confidence: 99%